2013
DOI: 10.7567/jjap.52.04cr07
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Photovoltaic Properties of Polysilane-Based Solar Cells

Abstract: Polysilane/C 60-based solar cells were fabricated and investigated. Two-types of devices with bulk heterojunction and heterojunction structures were examined and characterized. Addition of silicon-based polymer to the organic solar cells improved the conversion efficiency by wide optical absorption and high carrier mobility. Microstructures of the solar cells were investigated by using X-ray diffraction and transmission electron microscopy. Energy levels in the present solar cells were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Since organic thin-film solar cells have the advantages of low cost, flexibility, and being lightweight, the photovoltaic and optical properties of the organic solar cells have been studied [1][2][3][4][5][6][7]. Polysilane is a p-type semiconductor and has been used as an electrical conductive material and photovoltaic systems [7][8][9][10][11][12][13][14]. Polysilanes are known as σ-conjugate polymers, and their hole mobility is 10 −4 cm 2 V −1 s −1 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since organic thin-film solar cells have the advantages of low cost, flexibility, and being lightweight, the photovoltaic and optical properties of the organic solar cells have been studied [1][2][3][4][5][6][7]. Polysilane is a p-type semiconductor and has been used as an electrical conductive material and photovoltaic systems [7][8][9][10][11][12][13][14]. Polysilanes are known as σ-conjugate polymers, and their hole mobility is 10 −4 cm 2 V −1 s −1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polysilanes are known as σ-conjugate polymers, and their hole mobility is 10 −4 cm 2 V −1 s −1 [7]. Although the polysilanes could be applied to p-type semiconductors on organic thinfilm solar cells, few studies on polysilane-based solar cells have been reported [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their photoconductive properties, polysilanes may be applied to novel organic semiconductor devices. Some researchers investigated the photovoltaic properties of bulk heterojunction solar cells using C 60 and [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM) as electron acceptors and polysilanes as electron donors [ 84 , 85 , 86 , 87 ]. Furthermore, composite materials composed of polysilanes and EMFs may exhibit improved electronic properties as compared with those of empty fullerene-based materials.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Polysilanes are promising candidates for the alternate hole transport materials because they are one-dimensional silicon-based materials [19] [20], and can provide good electrical, optical and photovoltaic properties [21] [22] [23] [24].…”
Section: Introductionmentioning
confidence: 99%